Design lab equipment tracking system using RFID - Muhammad Afandi , Baharudin (2012)
Monitoring laboratory equipment record is important to ensure every item is always in place. Generally, in and out equipment is handled manually by technician by writing down the equipment information, including time and date in equipment circulation form. Radio Frequency Identification (RFID) is one of the most practical and applicable in real implementation in-line with the nature where most of the systems are made computerized. In this project, I want to design laboratory equipment monitoring system using RFID technology. The RFID tag is tagged on the laboratory equipment where the tag contains laboratory equipment information and RFID reader is located at the door of each laboratory room. This monitoring system enables the head of laboratory and technician to monitor in-out equipment in actual environment and also increase the efficiency in managing equipment in the laboratory. Besides that, this system had been build using LABVIEW to create the block diagram for reading and the database system. The database for all the equipment information had been store in Microsoft Access and all the data including data logging from laboratory equipment can been seen from the output table. This system can easily access by laboratory staff to manage the equipment data. Benefits of the system include enhancement of the safety of University asset and reduce losses of assets and enhancement of the laboratory inventory control of equipment